On the univalence of an integral operator - PESCAR, Virgil (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
In this paper we introduce a new general integral operator for analytic functions in the open unit disk and we derive some criteria for univalence of this integral operator. Mathematics Subject Classification (2010): 30C45.